"How drie a Cinder this world is": Dissociation of Sensibility Redux. Issue 2 (November 2017) - Young, R. V.
Abstract : Although T.S. Eliot's phrase "dissociation of sensibility, " applied to the changes in poetry during the seventeenth century, made a stir when he introduced it in the review essay "The Metaphysical Poets" in 1921, it draws less attention now, and seems never to have been adequately explained. Since Eliot's claims are, in part, historical, it makes sense to consider the most historically significant changes occurring during the seventeenth century. It is during this period that the Reformation culminates and its effects become permanently established. Several recent studies of the Reformation by Charles Taylor, Brad Gregory, and Carlos M.N. Eire provide clues about how the religious and social cataclysm of the sixteenth and seventeenth centuries may have affected the poetic imagination. James Smith's classic essay, "The Metaphysical Poets, " offers a way of analyzing the figurative language of seventeenth-century poetry in order to grasp the impact of the religious change. The investigations by Taylor, Gregory, and Eire into the dynamic of the reforming tendency, beginning in the late Middle Ages, as well as the Scotist and nominalist intellectual underpinnings of the Reformation, prove to be pertinent to Eliot's insight regarding seventeenth-century poetry. The growth of individualism, personal anxiety about religious choice, and materialism portend a general movement towards secularization and influence the way poets see the world. Dissociation of sensibility can thus be understood as a result of the effect of the religious and social dislocations of the Reformation in the realm of poetry.